2017
DOI: 10.1016/j.bbamcr.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cAMP prevents apoptosis modulating Sirt3 protein level and OPA1 processing in cardiac myoblast cells

Abstract: Mitochondria, responding to a wide variety of signals, including oxidative stress, are critical in regulating apoptosis that plays a key role in the pathogenesis of a variety of cardiovascular diseases. A number of mitochondrial proteins and pathways have been found to be involved in the mitochondrial dependent apoptosis mechanism, such as optic atrophy 1 (OPA1), sirtuin 3 (Sirt3), deacetylase enzyme and cAMP signal. In the present work we report a network among OPA1, Sirt3 and cAMP in ROS-dependent apoptosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 51 publications
2
45
1
Order By: Relevance
“…Our recent studies have shown in CTNS−/− ciPTEC a higher mitochondrial fragmentation index associated with lower mitochondrial potential and mitochondrial cyclic AMP levels, rescued by 24 h treatment with 100 µM cysteamine or with the cell-permeant analogue of cyclic AMP, 8-Br-cAMP [8]. cAMP, in fact, is one of the major regulators of mitochondrial function [28][29][30] and dynamics [31]. In this contest, it should be noted that MEA has been found to improve mitochondrial function in mitochondrial respiratory chain diseases [32].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our recent studies have shown in CTNS−/− ciPTEC a higher mitochondrial fragmentation index associated with lower mitochondrial potential and mitochondrial cyclic AMP levels, rescued by 24 h treatment with 100 µM cysteamine or with the cell-permeant analogue of cyclic AMP, 8-Br-cAMP [8]. cAMP, in fact, is one of the major regulators of mitochondrial function [28][29][30] and dynamics [31]. In this contest, it should be noted that MEA has been found to improve mitochondrial function in mitochondrial respiratory chain diseases [32].…”
Section: Discussionmentioning
confidence: 96%
“…The protein expression levels of OPA1 were not significantly changed in mutated cells, compared to control ciPTEC cells (data not shown). However, the activity of OPA1 is also controlled at the post-translational level by proteolytic and acetylation changes [31]. Various stress conditions, including apoptotic stimulation, trigger the complete conversion of L-OPA1 into S-OPA1.…”
Section: Discussionmentioning
confidence: 99%
“…OPA1 is hyperacetylated under pathological stress and its GTPase activity is suppressed, whereas SIRT3, a NAD-dependent protein deacetylase (Onyango et al, 2002), can deacetylate OPA1 at Lys926 and Lys931 and restore its GTPase activity in vivo (Samant et al, 2014). These changes are accompanied by altered mitochondrial cAMP/PKA signaling (Signorile et al, 2017). Additionally, acetylation participates in regulation of mitophagy.…”
Section: Acetylation/deacetylationmentioning
confidence: 99%
“…Interesting, PHB2 has been found up-regulated in lymphocytes of MS patients [26]. OPA1 processing is also modulated by its acetylation status mediated by SIRT3 enzyme, a mitochondrial deacetylase that also plays an important role in apoptosis [20]. In this work we have analyzed the protein level, and proteolytic processing of OPA1 and its stress-associated regulators, OMA1, SIRT3, and PHB2 in PBMCs of MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Various stress conditions, including apoptotic stimulation are associated with the conversion of L-OPA1 into S-OPA1. The processing and activity of OPA1 is regulated by mitochondrial proteases, such as OMA1, cellular energetic condition [19], post-translational modification, such as acetylation status [20,21], and oxidative stress [20,22]. OMA1-mediated processing of OPA1 is a cellular stress response, in fact, although OMA1 is constitutively active, it display strongly enhanced activity in response to OS [23].…”
Section: Introductionmentioning
confidence: 99%